Processing technology of sapphire substrate
Through a phased processing process, combined with specific abrasive and polishing liquid, the processing challenges brought by the high hardness and stability of sapphire materials are solved, and efficient and high-quality sapphire substrate processing is achieved.
Patent Information
- Application Number
- CN202510237151.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-01
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-01
AI Technical Summary
The high hardness and high stability of sapphire materials make it difficult for traditional processing methods to ensure processing quality while maintaining high efficiency, and are prone to microcracks and scratches.
A processing process including cutting, pretreatment, coarse grinding, fine grinding, chemical mechanical polishing and cleaning is adopted. This process uses specific abrasive liquid and polishing liquid, combined with abrasive and polishing materials of different particle sizes, and gradually improves the surface quality of the sapphire substrate through staged grinding and polishing.
It effectively improves the processing efficiency of sapphire substrate, reduces the occurrence of micro cracks and scratches, ensures processing quality, and maintains the cleanliness and dryness of sapphire substrate.
Smart Images

Figure BDA0005293031910000061 
Figure BDA0005293031910000071 
Figure BDA0005293031910000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sapphire substrate processing, and more specifically, to a processing technology for a sapphire substrate. Background Art
[0002] Sapphire substrates are widely used in LED manufacturing. Due to their excellent optical transparency and thermal conductivity, sapphire substrates can effectively improve the light output efficiency and heat dissipation performance of LEDs. However, with the rapid development of science and technology, the requirements of the LED industry for sapphire finished products are becoming increasingly stringent. For example, in order to improve the luminous efficiency of LEDs and reduce costs, manufacturers have begun to require thinner sapphire substrates to reduce light absorption and reflection losses while reducing material costs. In addition, higher requirements are also placed on the surface quality of sapphire substrates, hoping that the size and number of surface defects are smaller, so as to further reduce the scattering and absorption of light and improve the light output efficiency and overall performance of LEDs.
[0003] However, the high hardness and high stability of sapphire materials pose great challenges to processing. Due to its extremely high hardness, traditional processing methods are difficult to maintain high efficiency while ensuring processing quality. For example, mechanical grinding usually uses extremely hard abrasives such as diamond grinding wheels for grinding. However, due to the extremely high hardness of sapphire, a large amount of heat and stress are easily generated during the grinding process, resulting in low processing efficiency, and it is easy to produce microcracks and scratches on the surface of the material, affecting the processing quality. Summary of the invention
[0004] In order to reduce microcracks and scratches generated in sapphire during the production process and improve production efficiency, the present application provides a processing technology for sapphire substrates.
[0005] The present application provides a sapphire substrate processing technology, which adopts the following technical solution: A sapphire substrate processing technology includes the following preparation steps: S1, cutting the sapphire to obtain sheet sapphire; S2, coating the surface of the flaky sapphire with a layer of silicone oil to obtain a pretreated flaky sapphire; S3, using a silk polishing pad to perform double-sided rough grinding of the pretreated flaky sapphire to obtain rough-ground flaky sapphire, wherein a rough grinding liquid is required in the rough grinding process, and the rough grinding liquid is composed of silicon nitride, silicon dioxide, a dispersant, a surfactant, a penetrant and water in a weight ratio of (5-9): (3-5): (2-3): (1-2): (0.5-1): 13; S4. Use a non-woven polishing pad to fine-grind the coarse-ground flaky sapphire to obtain fine-grinded flaky sapphire. A fine-grinding liquid is required in the fine-grinding process. The fine-grinding liquid is composed of aluminum oxide, tungsten carbide, sodium hydroxyethyl cellulose, phosphoric acid, defoaming agent, stearic acid, suspending agent and water in a weight ratio of (4-6): (3-5): (2-3): (1-2): (0.5-0.8): (2-3): (2-4): 15; S5. Use a polyurethane polishing pad to perform chemical mechanical polishing on the finely ground flaky sapphire to obtain a polished flaky sapphire. A polishing liquid is required during the polishing process. The polishing liquid is composed of silicon nitride, aluminum oxide, trishydroxymethylaminomethane, diethylenetriaminepentaacetic acid, polyol fatty acid ester, ricinoleic acid, hydroxyethyl cellulose and water in a weight ratio of (3-6): (4-6): (1-2): (0.5-1): (2-3): (4-6): (1-2): 15; S6. Immerse the polished sapphire sheet in a cleaning solution, take it out, clean it with purified water, and dry it to obtain a sapphire substrate. The cleaning solution is composed of an oxidant, neopentyl glycol, isopropanolamine, sodium dodecyl sulfate and purified water in a weight ratio of (0.5-1):(3-5):(2-4):(1-3):20.
[0006] By adopting the above technical solution, through a series of sophisticated processing steps and optimized grinding liquid formula, the processing challenges brought by the high hardness and high stability of sapphire materials are effectively solved, the processing efficiency of sapphire substrates is improved, the processing quality is guaranteed, the generation of microcracks and scratches is reduced, and the cleanliness and dryness of sapphire substrates are maintained.
[0007] Step S2 coats the sapphire surface with a layer of silicone oil. This pretreatment step may help reduce heat and stress accumulation during subsequent grinding and may improve abrasive adhesion and uniformity.
[0008] In step S3, a silk polishing pad and a specific first grinding liquid are used for double-sided rough grinding. Silicon nitride and silicon dioxide in the grinding liquid are used as abrasives to effectively remove a large amount of material on the sapphire surface. At the same time, the addition of dispersants, surfactants and penetrants helps to improve the dispersibility and permeability of abrasives, reduce heat and stress during grinding, and thus reduce the generation of microcracks and scratches.
[0009] In step S4, a non-woven polishing pad and a second grinding liquid are used for fine grinding. Aluminum oxide and tungsten carbide, as finer abrasives, can further remove the marks left by rough grinding and improve the surface quality. At the same time, additives such as sodium hydroxyethyl cellulose in the grinding liquid help maintain the stability and uniformity of the abrasive, further improving the processing quality.
[0010] Step S5 uses a polyurethane polishing pad and polishing liquid for chemical mechanical polishing. The silicon nitride and aluminum oxide in the polishing liquid act as abrasives, and together with tris(hydroxymethyl)aminomethane, diethylenetriaminepentaacetic acid, etc., they can form a protective film on the sapphire surface, while removing a very small amount of material to achieve a very high surface finish.
[0011] Specific rough grinding liquid, fine grinding liquid and polishing liquid are used in this application, so that difficult-to-clean stains may remain on the surface of the sapphire substrate, and the specific cleaning liquid in this application can effectively remove the stains.
[0012] Preferably, the silicone oil is amino silicone oil.
[0013] By adopting the above technical solution, amino silicone oil not only has excellent lubricity and adhesion, but can also effectively reduce the direct impact of mechanical grinding on the sapphire surface during the rough grinding stage and reduce processing damage; at the same time, its good chemical stability can also ensure that it will not react adversely with the grinding fluid or polishing fluid during the processing process, affecting the processing effect.
[0014] Preferably, the average particle size of the silicon nitride is 50-100 nm, and the average particle size of the silicon dioxide is 20-50 nm.
[0015] By adopting the above technical solution, the average particle size of silicon nitride and silicon dioxide is optimized, ensuring the uniform dispersion and efficient use of the abrasive, improving the grinding efficiency, and reducing the accumulation of heat and stress during the processing, effectively avoiding microcracks and scratches on the sapphire surface. Secondly, the abrasive in this particle size range can form fine and uniform scratches, which helps to quickly remove surface defects and improve the surface finish and flatness of the sapphire substrate. In addition, the optimized particle size also enhances the stability and fluidity of the grinding liquid, making the grinding process more continuous and uniform, further improving the processing quality.
[0016] Preferably, the average particle size of the aluminum oxide is 20-50 nm, and the average particle size of the tungsten carbide is 50-90 nm.
[0017] By adopting the above technical solution, the average particle size of aluminum oxide and the average particle size of tungsten carbide are optimized to ensure uniformity and efficiency during the grinding process, thereby improving processing efficiency and surface quality. Secondly, the smaller particle size of aluminum oxide helps to refine scratches and improve the smoothness of the sapphire surface, while the moderate particle size of tungsten carbide enhances its ability to remove surface defects. The combination of the two makes the surface of the sapphire substrate flatter and smoother. In addition, the optimization of this particle size range also helps to reduce the consumption of grinding fluid and equipment wear, reducing processing costs.
[0018] Preferably, the average particle size of the silicon nitride is 5-10 nm, and the average particle size of the aluminum oxide is 10-20 nm.
[0019] By adopting the above technical solution, the average particle size of silicon nitride and the average particle size of aluminum oxide are optimized, so that the polishing liquid can penetrate deeper into the tiny defects on the sapphire surface, improving the processing accuracy and surface finish. Secondly, the ultra-fine silicon nitride and aluminum oxide particles can form more uniform and delicate scratches during the grinding process, reducing the depth and number of surface scratches, making the processed sapphire surface smoother and brighter. In addition, the optimization of this particle size range also helps to reduce the accumulation of heat and stress during the grinding process, further reducing the generation of microcracks and scratches.
[0020] Preferably, the penetrant is obtained by mixing sodium polyacrylate and sodium phosphate in a weight ratio of 1 (3-5).
[0021] By adopting the above technical solution, the interfacial tension between the grinding liquid and the sapphire material can be effectively reduced, the wettability and permeability of the grinding liquid can be enhanced, and the grinding particles can be more evenly distributed on the material surface, thereby improving the grinding efficiency.
[0022] Preferably, the suspending agent is composed of polyvinyl alcohol and polyvinyl pyrrolidone in a weight ratio of 1:(2-3).
[0023] By adopting the above technical solution, the suspension stability of abrasive particles in the grinding liquid can be improved, the particles can be prevented from settling and agglomerating, and the abrasive particles can be ensured to act evenly and continuously on the surface of the sapphire material during the grinding process. At the same time, the suspending agent can also effectively improve the rheological properties of the grinding liquid, making it easier to spread and penetrate on the surface of the material, further improving the grinding efficiency and processing quality.
[0024] Preferably, a cutting fluid is required in the cutting process of step S1, and the cutting fluid is composed of polyethylene glycol laurate, sodium isophenylpropane sulfonate, polyethylene oxide, trisodium methylglycine diacetate and water in a weight ratio of (2-3): (1-2): (2-4): (0.5-1): 8.
[0025] The ingredients in the cutting fluid work together to effectively reduce friction and heat during the cutting process, reduce damage and cracks to the sapphire crystal, and improve cutting efficiency. At the same time, the cutting fluid also has good lubricity and cooling effects, ensuring the flatness and smoothness of the cut surface, laying a good foundation for subsequent processing steps.
[0026] Preferably, the rough grinding load in step S2 is 15-25 g / cm 2 , the grinding speed is 45-75 rpm, the coarse grinding liquid flow rate is 50-100 ml / min, and the grinding time is 25-30 min.
[0027] By adopting the above technical solutions, the rough grinding load, grinding speed, polishing liquid flow rate and grinding time and other parameters can be accurately controlled to improve the rough grinding quality and efficiency of sapphire. The rough grinding load is set at 15-25g / cm 2 range, ensuring effective contact between the abrasive and the sapphire surface and improving the grinding efficiency; the grinding speed is controlled at 45-75 rpm, which not only ensures the uniformity of grinding, but also avoids heat accumulation and surface damage caused by too high a speed; the polishing liquid flow rate is set at 50-100ml / min, which ensures sufficient lubrication and cooling during the grinding process and further reduces the generation of surface scratches and microcracks; the grinding time is controlled at 25-30 minutes, which not only ensures sufficient grinding time to remove surface defects, but also avoids excessive wear caused by too long grinding.
[0028] Preferably, the fine grinding load in step S3 is 25-60 g / cm 2 , the grinding speed is 80-120 rpm, the fine grinding liquid flow rate is 150-250ml / min, and the grinding time is 10-30min.
[0029] By adopting the above technical solution, parameters such as fine grinding load, grinding speed, polishing liquid flow rate and grinding time can be accurately controlled to improve the fine grinding quality and efficiency of sapphire, providing a high-quality processing foundation for subsequent polishing steps.
[0030] Preferably, the polishing load in step S4 is 100-150 g / cm 2 , polishing speed is 100-200 rpm, polishing liquid flow rate is 100-200ml / min, and polishing time is 120-240min.
[0031] By adopting the above technical solutions, the polishing load, grinding speed, polishing liquid flow rate and grinding time and other parameters can be accurately controlled to improve the surface quality and processing efficiency of sapphire and meet the manufacturing requirements of high-precision optical components. The polishing load is set at 100-150g / cm 2 The range ensures sufficient pressure and contact area between the polishing pad and the sapphire, and promotes the uniform distribution and high efficiency of the polishing agent. The polishing speed is controlled at 100-200 rpm. The speed within this range not only ensures the high efficiency of polishing, but also avoids surface damage caused by excessive speed. The polishing liquid flow rate is set to 100-200ml / min, which ensures the continuous supply of polishing liquid during the polishing process and effectively reduces the generation of surface scratches and fog defects.
[0032] In summary, this application has the following beneficial effects: 1. This application effectively solves the challenges of high hardness and high stability in the processing of sapphire materials by optimizing the steps of cutting and pretreatment, staged grinding and lapping, chemical mechanical polishing, cleaning and drying. This solution improves processing efficiency while ensuring processing quality, reducing the generation of microcracks and scratches, and provides an efficient and reliable processing method for the preparation of sapphire substrates. DETAILED DESCRIPTION Example
[0033] Amino silicone oil was purchased from Shandong Huachen New Materials Co., Ltd., model HC.
[0034] Example 1 A sapphire substrate processing technology includes the following preparation steps: S1, cutting the sapphire to obtain sheet sapphire; S2, coating the surface of the flaky sapphire with a layer of silicone oil to obtain a pretreated flaky sapphire; S3, using a silk polishing pad to perform double-sided rough grinding of the pretreated flaky sapphire to obtain a rough-ground flaky sapphire, wherein a rough grinding solution is required in the rough grinding process, and the rough grinding solution is composed of silicon nitride, silicon dioxide, a dispersant (microcrystalline wax), a surfactant (Tween), a penetrant (sodium polyacrylate) and water in a weight ratio of 5:3:2:1:0.5:13; The average particle size of silicon nitride is 50-60nm, and the average particle size of silicon dioxide is 20-30nm; The rough grinding load in step S2 is 15 g / cm 2 , grinding speed is 45 rpm, coarse grinding liquid flow rate is 50 ml / min, and grinding time is 25 min; S4, using a non-woven polishing pad to fine-grind the coarse-ground flaky sapphire to obtain fine-grinded flaky sapphire, wherein a fine-grinding liquid is required in the fine-grinding process, and the fine-grinding liquid is composed of aluminum oxide, tungsten carbide, sodium hydroxyethyl cellulose, phosphoric acid, a defoaming agent (propanol), stearic acid, a suspending agent (polyvinyl alcohol) and water in a weight ratio of 4:3:2:1:0.5:2:2:15; The average particle size of aluminum oxide is 20-50nm, and the average particle size of tungsten carbide is 50-90nm; The fine grinding load in step S3 is 25 g / cm 2 , grinding speed is 80 rpm, grinding liquid flow rate is 150 ml / min, grinding time is 10 min; S5. Using a polyurethane polishing pad to perform chemical mechanical polishing on the fine-ground flaky sapphire to obtain a polished flaky sapphire. A polishing liquid is required during the polishing process. The polishing liquid is composed of silicon nitride, aluminum oxide, trishydroxymethylaminomethane, diethylenetriaminepentaacetic acid, polyol fatty acid ester (glycerol fatty acid ester), ricinoleic acid, hydroxyethyl cellulose and water in a weight ratio of 3:4:1:0.5:2:4:1:15. The average particle size of silicon nitride is 5-10nm, and the average particle size of aluminum oxide is 10-20nm; The polishing load in step S4 is 100 g / cm 2 , polishing speed is 100 rpm, polishing liquid flow rate is 100 ml / min, polishing time is 120 min; S6. Soak the polished sapphire sheet in a cleaning solution, take it out, clean it with purified water, and dry it to obtain a sapphire substrate. The cleaning solution is composed of an oxidant, neopentyl glycol, isopropanolamine, sodium dodecyl sulfate and purified water in a weight ratio of 0.5:3:2:1:20.
[0035] The difference between Example 2-3 and Example 1 is that the raw materials, dosage and experimental parameters of the processing technology of the sapphire substrate are different. The specific differences are shown in Table 1: Example 4 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the average particle size of silicon dioxide is 50-60nm.
[0036] Example 5 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the average particle size of aluminum oxide is 50-60nm.
[0037] Example 6 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the average particle size of silicon nitride is 5-10 nm.
[0038] Example 7 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the penetrant is obtained by mixing sodium polyacrylate and sodium phosphate in a weight ratio of 1:3.
[0039] Example 8 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the penetrant is obtained by mixing sodium polyacrylate and sodium phosphate in a weight ratio of 1:5.
[0040] Example 9 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 1 is that the suspending agent is composed of polyvinyl alcohol and polyvinyl pyrrolidone in a weight ratio of 1:2.
[0041] Example 10 A processing technology for a sapphire substrate. The difference between this embodiment and embodiment 7 is that the suspending agent is composed of polyvinyl alcohol and polyvinyl pyrrolidone in a weight ratio of 1:3.
[0042] Comparative Example Comparative Example 1 A processing technology for a sapphire substrate. The difference between this comparative example and Example 1 is that step S2 is omitted.
[0043] Comparative Example 2 A processing technology for a sapphire substrate. The difference between this comparative example and Example 1 is that diamond powder is used in the coarse grinding liquid instead of silicon nitride.
[0044] Comparative Example 3 A processing technology for a sapphire substrate. The difference between this comparative example and Example 1 is that diamond powder is used instead of tungsten carbide in the fine grinding liquid.
[0045] Comparative Example 4 A processing technology for a sapphire substrate. The difference between this comparative example and Example 1 is that diamond powder is used in the polishing liquid instead of silicon nitride.
[0046] Comparative Example 5 A processing technology for a sapphire substrate. The difference between this comparative example and Example 1 is that the cleaning liquid is purchased from Dongguan Hill Metal Materials Co., Ltd. and the model is HR-332.
[0047] Detection method / test method Number of cracks and scratches: 50 sapphire substrates were prepared according to the preparation processes of Examples 1-10 and Comparative Examples 1-7, and the sapphire substrates were observed using an atomic force microscope at 500 times magnification to count the total number of cracks and scratches.
[0048] Surface roughness: Measure the sapphire substrate using a roughness tester.
[0049] Residual contaminants: The sapphire substrate wafer was scanned by electron microscope to observe the residual contaminants on its surface. The experimental data is shown in Table 2: Table 2 Experimental data of Examples 1-10 and Comparative Examples 1-5 Comparing Example 1 with Comparative Example 1, the total number of cracks and scratches in Comparative Example 1 is 5, and the surface roughness is greater than that in Example 1, indicating that coating the flaky sapphire with silicone oil is beneficial to reducing the number of cracks and scratches during the processing of the sapphire substrate, while improving the surface uniformity of the sapphire substrate.
[0050] Comparing Example 1 with Comparative Examples 2-4, the total number of cracks and scratches in Comparative Examples 2-4 are 8, 9, and 11, respectively; the surface roughness is greater than that in Example 1, indicating that by properly matching solid particles during rough grinding, fine grinding, and polishing, the number of cracks and scratches occurring during the processing of the sapphire substrate can be reduced, while the surface uniformity of the sapphire substrate can be improved.
[0051] Comparing Example 1 with Comparative Example 5, the surface roughness of Comparative Example 5 is greater than that of Example 1, and the number of particles larger than 0.5 μm in Comparative Example 5 is 11, indicating that the use of the cleaning solution in the present application is beneficial for removing residual pollutants in the process.
[0052] Comparing Example 1 with Examples 4-6, the total number of cracks and scratches in Examples 4-6 are 3, 4, and 3, respectively, and the surface roughness is greater than that in Example 1, indicating that optimizing the average particle size of the solid particles is beneficial to reducing the number of cracks and scratches during the processing of the sapphire substrate, while improving the surface uniformity of the sapphire substrate.
[0053] Comparing Example 1 with Examples 7-8, the surface roughness of Examples 7-8 is less than that of Example 1, indicating that using sodium polyacrylate and sodium phosphate in a specific ratio is beneficial to improving the surface roughness of the sapphire substrate.
[0054] By comparing Example 1 with Example 9, the surface roughness of Example 9 is less than that of Example 1; By comparing Example 7 with Example 10, the surface roughness of Example 7 is less than that of Example 10; It can be seen from the experimental data of Examples 1, 9 and 7, 10 that the use of polyvinyl alcohol and polyvinyl pyrrolidone in a specific ratio is beneficial to improving the surface uniformity of the sapphire substrate.
[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A sapphire substrate processing technology, characterized in that: The method comprises the following preparation steps: S1, cutting the sapphire to obtain sheet sapphire; S2, coating the surface of the flaky sapphire with a layer of silicone oil to obtain a pretreated flaky sapphire; S3, using a silk polishing pad to perform double-sided rough grinding of the pretreated flaky sapphire to obtain rough-ground flaky sapphire, wherein a rough grinding liquid is required in the rough grinding process, and the rough grinding liquid is composed of silicon nitride, silicon dioxide, a dispersant, a surfactant, a penetrant and water in a weight ratio of (5-9): (3-5): (2-3): (1-2): (0.5-1): 13; S4. Use a non-woven polishing pad to fine-grind the coarse-ground flaky sapphire to obtain fine-grinded flaky sapphire. A fine-grinding liquid is required in the fine-grinding process. The fine-grinding liquid is composed of aluminum oxide, tungsten carbide, sodium hydroxyethyl cellulose, phosphoric acid, defoaming agent, stearic acid, suspending agent and water in a weight ratio of (4-6): (3-5): (2-3): (1-2): (0.5-0.8): (2-3): (2-4): 15; S5. Using a polyurethane polishing pad to chemically mechanically polish the finely ground flaky sapphire to obtain a polished flaky sapphire. A polishing liquid is required during the polishing process. The polishing liquid is composed of silicon nitride, aluminum oxide, trishydroxymethylaminomethane, diethylenetriaminepentaacetic acid, polyol fatty acid ester, ricinoleic acid, hydroxyethyl cellulose and water in a weight ratio of (3-6): (4-6): (1-2): (0.5-1): (2-3): (4-6): (1-2): 15; S6. Soak the polished sapphire sheet in a cleaning solution, take it out, clean it with purified water, and dry it to obtain a sapphire substrate. The cleaning solution is composed of an oxidant, neopentyl glycol, isopropanolamine, sodium dodecyl sulfate and purified water in a weight ratio of (0.5-1):(3-5):(2-4):(1-3):
20.
2. The sapphire substrate processing technology according to claim 1, characterized in that: The average particle size of the silicon nitride is 50-100 nm, and the average particle size of the silicon dioxide is 20-50 nm.
3. The sapphire substrate processing technology according to claim 2, characterized in that: The average particle size of the aluminum oxide is 20-50 nm, and the average particle size of the tungsten carbide is 50-90 nm.
4. The sapphire substrate processing technology according to claim 1, characterized in that: The average particle size of the silicon nitride is 5-10 nm, and the average particle size of the aluminum oxide is 10-20 nm.
5. The sapphire substrate processing technology according to claim 4, characterized in that: The penetrant is obtained by mixing sodium polyacrylate and sodium phosphate in a weight ratio of 1 (3-5).
6. The sapphire substrate processing technology according to claim 4, characterized in that: The suspending agent is composed of polyvinyl alcohol and polyvinyl pyrrolidone in a weight ratio of 1: (2-3).
7. The sapphire substrate processing technology according to claim 1, characterized in that: In step S1, a cutting fluid is required during the cutting process. The cutting fluid is composed of polyethylene glycol laurate, sodium isophenylpropane sulfonate, polyethylene oxide, trisodium methylglycine diacetate and water in a weight ratio of (2-3): (1-2): (2-4): (0.5-1):
8.
8. The sapphire substrate processing technology according to claim 1, characterized in that: The rough grinding load in step S2 is 15-25 g / cm 2 , the grinding speed is 45-75 rpm, the polishing liquid flow rate is 50-100 ml / min, and the grinding time is 25-30 min.
9. The sapphire substrate processing technology according to claim 1, characterized in that: In step S3, the fine grinding load is 25-60 g / cm2, the grinding speed is 80-120 rpm, the polishing liquid flow rate is 150-250 ml / min, and the grinding time is 10-30 min.
10. The sapphire substrate processing technology according to claim 1, characterized in that: The polishing load in step S4 is 100-150 g / cm 2 , polishing speed is 100-200 rpm, polishing liquid flow rate is 100-200ml / min, and polishing time is 120-240min.
Citation Information
Patent Citations
Sapphire wafer grinding and polishing method
CN110744362A
Polishing and cleaning method, cleaning agent, and grinding and cleaning kit
CN116323882A
Polishing composition
WO2017002705A1